Evaluating the relationship between retail and technology companies’ share prices with earnings and net cash flow in the context of South Africa and America (USA) - Tiquin, Cal (University of the Witwatersrand, Johannesburg, 2023)
Background: The informational value of accounting information is becoming increasingly important within the context of the modern information age. Research in this regard is lacking within the South African context, and within the technological sector. Purpose: The purpose of this research study is to test if the explanatory power of net earnings and cash flow differed for separate sectors of stock exchanges. Methodology: Four samples, representing the technology and retail sectors of both the JSE and the NYSE were collected and analysed in terms of an Ohlson (1995) model for a five year time period, from 2017 to 2021 (inclusive). Using a linear panel data regression model with secondary data, the explanatory power of both cash flow and earnings were compared between the different sectors. Findings: The results showed that the explanatory power of cash flow was greater than the explanatory power of net earnings on the NYSE for the technology sector, while the opposite was true for a traditional, retail sector. No significant regression results were attained for the JSE. Implications: The findings of this research provide valuable insight into the informational value of accounting information, and how it may differ between sectors. It may also assist regulatory bodies, Stock exchanges and investors in determining if different accounting information should be presented or prioritised for different sector
A research report submitted in partial fulfillment of the degree of Master of Commerce University of the Witwatersrand, 2023
Keywords: Earnings, Explanatory power; Cash flow; NYSE; JSE; Ohlson model; Predictive power; Retail sector; Share price; UCTD; Technology sector; Value relevance; SDG-8: Decent work and economic growth